2020
DOI: 10.1002/jsfa.10677
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted extraction of collagen from clown featherback (Chitala ornata) skin: yield and molecular characteristics

Abstract: BACKGROUND: Clown featherback (Chitala ornata) skin, a by-product from the filleting process line, could serve as a good aquatic collagenous source. Nevertheless, the typical collagen extraction method is a time-consuming process providing a relatively low yield. Ultrasound had been reported to be an alternative technique for enhancing the extraction efficiency of several compounds, although the harsh conditions of ultrasound could affect their physicochemical and molecular characteristics. Thus, the applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 57 publications
(163 reference statements)
2
72
0
Order By: Relevance
“…This is because ultrasonication favors the penetration of extraction solvents into the internal structure and therefore can enhance mass transfer, resulting in the increase of extraction yield 26 . Petcharat et al 9 found that increased yield of protein extracted from frog skin could be obtained with UAP at higher amplitude and longer ultrasonication time. In addition, Choi, et al 27 reported that UAP had an impact on alleviating protein extraction yield from Silkworm pupae where the highest yield was obtained with a 5 min ultrasonication time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This is because ultrasonication favors the penetration of extraction solvents into the internal structure and therefore can enhance mass transfer, resulting in the increase of extraction yield 26 . Petcharat et al 9 found that increased yield of protein extracted from frog skin could be obtained with UAP at higher amplitude and longer ultrasonication time. In addition, Choi, et al 27 reported that UAP had an impact on alleviating protein extraction yield from Silkworm pupae where the highest yield was obtained with a 5 min ultrasonication time.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, with a 10-min ultrasonication time, there was a decrease in protein recovery with amplitude increased. It had been previously shown that the higher energy from ultrasound, particularly with higher amplitude and ultrasonication time, generally resulted in higher protein extraction yield from rice bran 10 , fish skin 9 and edible insects 27 . However, Petcharat et al 9 showed that energy from UAP could destroy the insect powder matrix, in which some other co-extraction soluble solids could also be leached.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations